Precarious Work, Gender Roles, and the Use of Work-Life Balance Programs in Academia - Enoh, Eno Ibok Jackson (University of Lethbridge, Dhillon School of Business, 2019)
This thesis examined the experiences of contract academic staff (CAS) regarding their use of work-life balance programs (WLBPs). As precarious employees, CAS are subject to work conditions that put them in a bind between surviving as precarious workers and meeting the demands of their work and family lives. As such, a clearer picture of how such highly-skilled professionals utilize WLBPs to achieve WLB is required. Adopting the phenomenology qualitative research approach, I used NVivo to analyze the data obtained from in-depth, semi-structured interviews conducted with ten research participants. Four themes emerged: precarious work, support and performance, gendered aspects of academia, and precarious workers’ use of WLBPs. Results showed that male and female CAS adopted similar WLBPs as boundary management strategies to integrate and/or separate their work and family obligations. The limitations and implications of the research for theory and practice were discussed and recommendations were made for future research.